Implementation Of Business Process Reengineering (BPR) In Courier Business Services To Improve The Quality Of Public Services - Mira Veranita; Bambang Heru Purwanto (Jurnal Manajemen Pelayanan Publik, 2023)
This research was conducted to determine the implementation of business process reengineering to improve the quality of public services in the courier business. The research method used is mixed-method: concurrent embedded with a service quality measurement method: service performance (Servperf), which is equipped with a customer satisfaction index and an important performance analysis of 200 public service users. PT Pos Indonesia has implemented re-engineering of its business processes, especially by implementing information technology and digital transformation to improve the quality of its services. Based on the results of quantitative analysis, the quality of service at PT Pos Indonesia is classified as good, even though it has not yet received complete trust from the public, with public service priorities that must be prioritized regarding clarity of service standards, speed of digital access, ease of use of features and shortcuts in digital applications, politeness, and employee attitudes in providing services. Suggestions that can be given in implementing business process reengineering to improve the quality of service to the public are: increasing the socialization of the company's vision and mission regarding services; paying attention to employee incentives; increasing employee skills to face rapid technological developments and market trends; preparing and retaining the best employees; developing a flexible strategy to meet workforce needs; and realizing transformation, which is the company's action plan.